A 50-Year-Old Female with Recurrent Stroke-Like Episodes and A Diagnosis of Systemic Lupus Erythematosus - Sathyapriya, S. V.; Reddy, M Bhavana; Padma, V.; Reddy, Sharath Chandra; Vignesh, Veera (Journal of Neonatal Surgery, 2025)
Systemic lupus erythematosus (SLE) is a multisystem autoimmune disorder that can present with neurological manifestations, including stroke. Antiphospholipid syndrome (APS), a common complication of SLE, increases the risk of recurrent thrombotic events. We report a 50-year-old female with hypertension and diabetes who initially presented with acute left-sided hemiparesis and was diagnosed with an ischemic stroke in the right middle cerebral artery (MCA) territory. She was treated with dual antiplatelet therapy and statins, leading to partial recovery. Two weeks later, she developed worsening left-sided weakness progressing to hemiplegia, with MRI showing new infarcts. A hypercoagulability workup revealed positive lupus anticoagulant, anticardiolipin antibodies, and anti-β2 glycoprotein I antibodies, confirming APS. Further testing for autoimmune disorders showed positive ANA and anti-dsDNA, leading to a diagnosis of SLE. The patient was started on anticoagulation, hydroxychloroquine, and corticosteroids, resulting in clinical improvement. This case highlights the importance of considering SLE and APS in patients with recurrent strokes, as early diagnosis and appropriate treatment can significantly reduce morbidity and prevent further thrombotic events.